Faktor-Faktor Yang Mempengaruhi Produksi Tanaman Sayur Kubis (Barissca oleracea var. capitata) Di Kelurahan Rurukan Kecamatan Tomohon Timur Kota Tomohon - Manaung, Elshaday Beckya; Benu, Noortje Marsellanie; Baroleh, Jenny (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This study aims to analyze the factors that influence the production of cabbage vegetable crops in Rurukan Village, East Tomohon District, Tomohon City. This research lasted for one month starting from April to May 2024. The data collected in this research the data used are primary data obtained from direct interviews with cabbage vegetable farmers is simple random sampling at 30 respondent, and secondary data obtained in this study are from the village office and extension center. The results showed that the most influential production factors in cabbage vegetable farming in the village of Rurukan were land area and pesticides with significance <0.05. While organic fertilizer, urea fertilizer, phonska fertilizer, herbicides and labor do not have a significant influence on the production of cabbage vegetable crops.